Vietnam's rice-producing regions (1.3 M ha) cope with water shortage, drought, and salinity intrusion by applying the CCAFS' Climate-Smart Maps and Adaptation Plans - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Vietnam's Department of Crop Production (DCP) has been implementing the Climate-Smart Maps and Adaptation Plans (CS-MAP) for the rice production in Mekong River Delta (MRD). To address the salinity intrusion during the Winter-Spring season 2019-2020 and 2020-2021, cropping adjustments guided by CS-MAP were applied in more than 800,000ha and 500,000ha, respectively. CS-MAP has also been applied to other major rice-producing areas of Red River Delta and Northern Midlands (for irrigation management) and South Central Coast (for drought and salinity intrusion).